L’art radiophonique : histoire d’un médium de masse devenu médium artistique - John Barber (Appareil)
This essay outlines the history and several examples of radio art to demonstrate the use of radio beyond its traditional role of commerce and/or control. Instead, using the affordances, infrastructure, and technologies of radio, radio art seeks to produce creative artifacts within the radio medium that both depend upon the medium for their creation, communication, and consumption and engage the listening audience with new artistic practices.